ANALISIS PENGENDALIAN KUALITAS PRODUK BATU BATA PADA UMKM ANUGRAH JAYA DENGAN METODE PLAN, DO, CHECK, ACT DAN USULAN PERBAIKAN MENGGUNAKAN 5W+1H - Akbar Filayati Sasando; Ayudhyah Eka Apsari (Bajang Institute, 2024)
UMKM Anugrah Jaya is a company engaged in clay processing, with one of itsproducts being bricks. In the period from January to December 2023, Anugrah JayaMSMEs produced 184,335 units of bricks, but as many as 35,227 units (20%) weredisabled. These types of defects include cracks, burns, and fractures. Of the totaldefects, cracks reached 2,139 units, burnt reached 29,019 units, and fracturesreached 4,069 units. This study aims to identify the factors causing defects in brickproducts and provide improvement proposals. The method used is PDCA (Plan, Do,Check, Action), with tools such as Pareto Diagram, Fishbone Diagram, p-chart, and5W+1H. The results showed that the factors causing disability are human, material,and method factors. Proposed improvements include regular inspections ofproduction processes, purchasing materials from one supplier to maintain consistentraw material quality, as well as training on the use of moisture measuring devicesand studies on more effective and efficient brick burning methods.